Novel Integrated Tiered Cumulative Risk Assessment of Heavy Metals in Food Homologous Traditional Chinese Medicine Based on a Real-Life-Exposure Scenario - Zuo, Tian-Tian; Jin, Hong-Yu; Chen, An-Zhen; Zhang, Lei; Kang, Shuai; Li, An-Ping; Gao, Fei; Wei, Feng; Yu, Jian-Dong; Wang, Qi; Yang, Jian-Bo; Ma, Shuang-Cheng (Frontiers in Pharmacology, 2022)
In order to serve population health better, the first integrated tiered decision tree for cumulative risk assessment of co-exposure of Pb-, Cd-, and As-associated health risks in food homologous traditional Chinese medicine (TCM) was designed, after measuring their concentrations by inductively coupled plasma-mass spectroscopy (ICP-MS). Basically, our three-step decision tree involving hazard quotient (HQ), hazard index (HI), and target-organ toxicity dose (TTD) modification of the HI method was developed to evaluate the potential risks of 949 batches of 15 types of food homologous TCM. To acquire a real-life exposure scenario, the cumulative risk assessment model was established by optimizing key parameters, such as ingestion rates, frequency, and duration of exposure to food homologous TCM based on questionnaire data. As a result, the mean concentrations of Pb, Cd, and As in 949 batches of food homologous TCM were 0.896, 0.133, and 0.192 mg/kg, respectively. The HQ values of As for Angelica sinensis (Oliv.) Diels and Houttuynia cordata Thunb. were 1.04 and 1.01, respectively, for females. Other HQs of Pb, Cd, or As in food homologous TCM were lower than 1 for both males and females. However, after rapid screening of the co-exposure health risks of heavy metals by the HI method, cumulative risk assessment results acquired by TTD modification of the HI method implied that the potential health risks associated with the co-exposure of Pb, Cd, and As in Lonicera japonica Thunb. and Houttuynia cordata Thunb. ingested as both TCM and food were of concern in the clinic. Additionally, the cumulative risks of Pb, Cd, and As in Mentha canadensis L., Chrysanthemum indicum L., and Zaocys dhumnades (Cantor) only used as food exceeded the human tolerance dose. Collectively, our innovation on the tiered strategy of decision tree based on a real-life exposure scenario provides a novel approach engaging in the cumulative risk assessment of heavy metals in food homologous TCM. All in all, such effort attempts to scientifically guide the rational use of TCM in the treatment of the complex diseases and the improvement of population health.